2013
DOI: 10.2320/jinstmet.j2012066
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Ni Aluminide Surface Layer Containing Yttrium at Different Depth by Molten Salt Electrodeposition and Cyclic Oxidation Resistance

Abstract: Attention has focused on a Ni aluminide containing a small amount of Y as a high oxidation resistant material, and preparation of a coating consisting of this material was attempted by the molten salt electrodeposition which is a low cost coating method. In the present study, the preparation of the coating consisting of this material was carried out by the electrodeposition of Ni using an aqueous solution as the electrolyte and the electrodeposition of Y and Al using a molten salt electrolyte. Furthermore, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2014
2014
2015
2015

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…On the contrary, Rommerskirchen 15) showed that for NiAl containing 0.39 mass% Y, the NiAlY alloys containing 30 and 29 mass% Y were deposited within the grains and along the grain boundaries, respectively. We also observed in a previous study 4) that for the Ni aluminide-coating specimen with the Y-containing layer, Y was deposited as the NiAlY alloy at the grain boundaries in the surface region of the Ni aluminide layer during the oxidation test. These results indicated that Y scarcely dissolved into the Ni aluminide.…”
Section: Morphologies Of Scale and Coating After Cyclicoxidation Testmentioning
confidence: 61%
See 2 more Smart Citations
“…On the contrary, Rommerskirchen 15) showed that for NiAl containing 0.39 mass% Y, the NiAlY alloys containing 30 and 29 mass% Y were deposited within the grains and along the grain boundaries, respectively. We also observed in a previous study 4) that for the Ni aluminide-coating specimen with the Y-containing layer, Y was deposited as the NiAlY alloy at the grain boundaries in the surface region of the Ni aluminide layer during the oxidation test. These results indicated that Y scarcely dissolved into the Ni aluminide.…”
Section: Morphologies Of Scale and Coating After Cyclicoxidation Testmentioning
confidence: 61%
“…1, and examined the cyclic-oxidation resistance of the Ni-10 at%Cr-8 at%Al alloy covered with these coatings. 4) As a result, we observed a high oxidation resistance when the Y-containing layer was formed in the vicinity of the center of the Ni aluminide layer ((b) and (c) processes). For the Ni aluminide-coatings with the Hfcontaining layer in the present study, however, when the Hfcontaining layer was formed in the vicinity of the center of the Ni aluminide layer, the cyclic-oxidation resistance was poor (Fig.…”
Section: Morphologies Of Scale and Coating After Cyclicoxidation Testmentioning
confidence: 81%
See 1 more Smart Citation
“…Furthermore, we showed that the coatings consisting of Ni aluminide (Ni 2 Al 3 ) were formed by the Al electrodeposition on the Ni plate or Ni film using a molten salt at 1023 K. 5,6) Though these coatings had a high oxidation resistance during the isothermal oxidation test, 5) they showed a mass loss due to spallation of a scale during a cyclic-oxidation test. 6) In order to improve a cyclic-oxidation resistance of the coating, we tried electrodeposition of Hf, 6,7) Zr 8) or Y 9) with Al using a molten salt at 1023 K. As a consequence, we succeeded in the preparation of a coating consisting of Ni aluminide containing small amounts of Hf, Zr or Y. Such coatings showed high cyclic-oxidation resistance in air at 1423 K.…”
Section: Introductionmentioning
confidence: 99%